2022
DOI: 10.3390/pharmaceutics14081709
|View full text |Cite
|
Sign up to set email alerts
|

Alginate/Chitosan-Based Hydrogel Film Containing α-Mangostin for Recurrent Aphthous Stomatitis Therapy in Rats

Abstract: Recurrent aphthous stomatitis (RAS) is a prevalent clinical disorder that causes mouth ulcers. Furthermore, corticosteroid treatment has been widely utilized for RAS therapy; however, it has side effects on the oral mucosa that limit its application. This study aimed to develop a novel RAS therapy with the natural ingredient α-mangostin, delivered by alginate and chitosan polymers-based hydrogel film (α-M Alg/Chi-HF). To prepare α-M Alg/Chi-HF, the solvent evaporation and casting methods were used, then charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…A study demonstrated that an in vivo investigation of αmangostin hydrogel films with a chitosan-alginate base for RAS therapy exhibited a favorable healing response, achieving a healing rate of 93% on the seventh day (Milanda et al, 2022). These promising outcomes have motivated us to conduct a Clinical Trial of α-mangostin Hydrogel Films with a Chitosan-Alginate Base with the aim of evaluating the clinical efficacy and safety in treating patients with RAS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study demonstrated that an in vivo investigation of αmangostin hydrogel films with a chitosan-alginate base for RAS therapy exhibited a favorable healing response, achieving a healing rate of 93% on the seventh day (Milanda et al, 2022). These promising outcomes have motivated us to conduct a Clinical Trial of α-mangostin Hydrogel Films with a Chitosan-Alginate Base with the aim of evaluating the clinical efficacy and safety in treating patients with RAS.…”
Section: Discussionmentioning
confidence: 99%
“…In a prior study, the development and assessment of αmangostin hydrogel films with a chitosan-alginate base for in vivo therapy of RAS were conducted using white Wistar rats as test subjects. The results showed a remarkable 93% healing rate within 7 days (Milanda et al, 2022). As a result, further investigations will be carried out to evaluate the clinical efficacy and safety of the chitosan-alginate-based α-mangostin hydrogel film in RAS patients.…”
mentioning
confidence: 94%
“…After that, the films were blotted with filter paper to remove excess water and measured by an UV-Vis spectrophotometer (Labtech, Hopkinton, MA, USA) at λ max = 265 nm. The ascorbic acid loading efficiency, amount of adsorbate, and loading capacity were calculated using the following formula [ 39 ]: where A 0 is the absorbance of the initial solution and A is the absorbance of the tested solution. …”
Section: Methodsmentioning
confidence: 99%
“…Chitosan is a product resulting from the partial deacetylation of chitin, possessing excellent antibacterial properties, adhesive power, oxygen permeability, non-toxicity, and easy biodegradation, holding great potential for medical applications, such as antibacterial medical dressings. 56 The crucial aspect of chitosan-based hydrogels for use in medical dressings is their host acceptance. Researchers have employed oxidized polysaccharides, like glucomannan, as environmentally friendly bio-crosslinkers.…”
Section: Potency Of Chitosan and Alginate As Natural Biodegradable Po...mentioning
confidence: 99%
“…The presence of reactive oxygen species (ROS) generated massively around damaged tissues can cause damage to DNA and proteins, inhibiting tissue regeneration. 56 …”
Section: Potency Of Chitosan and Alginate As Natural Biodegradable Po...mentioning
confidence: 99%